Students Knowledge of Faculty Evaluation in Tehran University of Medical Sciences Iran: Expectations Challenges Solutions - Sakineh Sharifian; Batool Amini; Salimeh Goharinezhad; Roghayeh Gandomkar (Kerman University of Medical Sciences, 2014)
Background & Objective: Evaluation of faculty members teaching activities by student is one of the commonly used methods the use of which has increased accordingly over time Therefore dynamic and meaningful participation of the students in the process is imperative The purpose of this study is to understand the knowledge of students of the evaluation process and its challenges and their solutions   Methods: This qualitative study was performed in 3 schools of Tehran University of Medical Sciences Iran in 2012 The opinions of student were collected during 3 focus group discussions with the participation of 19 students Participants were selected based on purposive sampling from among the student advisory committee All group discussions were recorded and then transcribed Data were analyzed by content analysis For credibility and authentication of data the peer monitoring and review method was used   Results: Major themes include the input challenges with 2 subthemes (barriers to participation and factors affecting evaluation) the process challenges with 2 subthemes (the evaluation time and students preferred format for evaluation) and the impact challenges with 2 subthemes (publication of results and reward and punishment evaluation systems)   Conclusion: The perceptions and awareness of students about the evaluation process and its application is important in the increasing of participation and their seriousness in answering questions Thus in order to reduce bias in the evaluation process it is recommended that suitable and timely information be given to students and faculty members courses be performed to familiarize them with the concept and application of evaluation and the evaluation questionnaires be revised